Fatal Pyogenic Liver abscess in Children: A Case report (Indian Internet Journal of Forensic Medicine and Toxicology, 2008)
A 3-year child was admitted to a private hospital with distended abdomen, decreased appetite, irritability and history of fever. He was promptly diagnosed as case of pyogenic liver abscess. Relevant treatment was instituted. Despite all efforts by the doctors the patient died. His relatives alleged medical negligence on the part of the treating physician, for which the medico-legal autopsy was conducted. In autopsy the cause of death was found to be septicemic shock as result of pyogenic liver abscess and its complications.
Keywords: Liver Abscess; Septicemia; Pyogenic; Children